2002
DOI: 10.1530/eje.0.1460855
|View full text |Cite
|
Sign up to set email alerts
|

Bone effects of hexarelin, a GH-releasing peptide, in female rats: influence of estrogen milieu

Abstract: Objective: The present study was performed to evaluate the potential influence of the estrogen milieu in modulating the effects of GH/IGF stimulation by a GH-releasing peptide, hexarelin (HEXA), on bone metabolism and mineral density in middle-aged female rats. Methods: HEXA was administered for 60 days (50 mg/kg s.c. twice a day) to intact and ovariectomized (OVX) 11-month-old female rats and changes in bone parameters were evaluated with respect to those of the same rats under baseline conditions and with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Kim et al () also discovered BFP‐2 corresponding to residues 140–154 of immature BMP‐7 and demonstrated its strong osteogenic activity and bone formation in vitro and in vivo. Other bioactive peptides with bone health activity, including calcinonin gene‐related peptide (CGRP), hexarelin, thrombin‐related peptide (TP508), osteogenic growth peptide (OGP), and calcitonin receptor fragment peptide (CRFP), were also investigated in vitro and in vivo (Komatsu, Hadjiargyrou, Udin, Trasolini, & Pentyala, ; Li, Ryaby, Carney, & Wang, ; Sibilia et al, ; Valentijn et al, ; Zhao et al, ). Osteogenic peptides with in vitro and in vivo activity are summarized in Table .…”
Section: Bone Health‐promoting Effect Of Bioactive Peptides Derived Fmentioning
confidence: 99%
“…Kim et al () also discovered BFP‐2 corresponding to residues 140–154 of immature BMP‐7 and demonstrated its strong osteogenic activity and bone formation in vitro and in vivo. Other bioactive peptides with bone health activity, including calcinonin gene‐related peptide (CGRP), hexarelin, thrombin‐related peptide (TP508), osteogenic growth peptide (OGP), and calcitonin receptor fragment peptide (CRFP), were also investigated in vitro and in vivo (Komatsu, Hadjiargyrou, Udin, Trasolini, & Pentyala, ; Li, Ryaby, Carney, & Wang, ; Sibilia et al, ; Valentijn et al, ; Zhao et al, ). Osteogenic peptides with in vitro and in vivo activity are summarized in Table .…”
Section: Bone Health‐promoting Effect Of Bioactive Peptides Derived Fmentioning
confidence: 99%
“…( 80 ) Moreover, a long‐acting GH secretagogue, hexarelin, prevents bone loss in the setting of androgen deficiency; however, after estrogen deficiency, efficacy of this compound seemed to be restricted to specific bone compartments in rats. ( 81 , 82 ) In a ghrelin knockout model, there was no effect on bone size, BMD, or fat deposition in 8‐week‐old mice. ( 83 ) In children, ghrelin secretion is not suppressed in response to diet, and thus, it is possible that skeletal effects of ghrelin are masked during growth, and a bone phenotype may only become apparent during aging.…”
Section: Potential Factors Regulating Bone Turnovermentioning
confidence: 99%
“…In vivo studies showed that intraperitoneal [ 5 ] as well as central administration [ 12 ] of ghrelin increases bone mineral density and mass through a mechanism independent of GH-IGF1 axis and appetite regulation, respectively. Consistently, synthetic GH secretagogues increase bone mineral density [ 13 ] and prevent gonadectomy-induced bone loss in the rat [ 14 , 15 ]. Data from clinical studies are limited but indicate a positive association between circulating ghrelin levels and bone mineral density in women [ 16 , 17 ] and elderly men [ 18 ].…”
Section: Introductionmentioning
confidence: 99%